Identification of atrial natriuretic factor within ventricular tissue in hamsters and humans with congestive heart failure. - Edwards, B S; Ackermann, D M; Lee, M E; Reeder, G S; Wold, L E; Burnett, J C, Jr (The Journal of Clinical Investigation, 1988)
In normal mammals, atrial natriuretic factor (ANF) is present within atrial myocardial cells but is absent from ventricular myocardium. In primitive organisms ANF is present within both atria and ventricle, suggesting that the ventricle may participate both in the synthesis and release of the hormone. The current study was designed to test the hypothesis that ventricular ANF develops as a homeostatic response to intravascular volume overload. Studies were performed on cardiac tissue obtained from (i) normal and cardiomyopathic hamsters, (ii) autopsied humans with and without cardiac disease, and (iii) living humans with congestive heart failure (CHF) undergoing diagnostic right ventricular endomyocardial biopsy. The myocardium was examined for the presence of immunoreactive ANF using a two-stage immunohistochemical technique, with nonimmune rabbit sera used as a negative control. There was unequivocal evidence of focal subendocardial deposits of immunoreactive ANF present in both of the ventricles of all six cardiomyopathic hamsters, four of five autopsied human subjects with CHF, and five of seven biopsied humans. No immunoreactive ANF was observed within the ventricular myocardium of control hamsters or normal humans. Utilizing crude tissue homogenates and radioimmunoassay techniques, the quantity of ANF was determined in cardiac atria, ventricles, and noncardiac skeletal muscle. Heart failure is characterized by a reduction in atrial ANF and an increase in ventricular ANF. This study demonstrates immunoreactive ANF is present within the ventricular myocardium in cardiomyopathic hamsters and humans with CHF, and suggests that the ventricle may be capable of responding to chronic volume overload by producing ANF. Images